Cover Art - Zhang, Yuhan (The Columbia Journal of Asia, 2025)
Abridged Artist Statement: Lungta (wind horse) is a mythical Tibetan creature symbolizing the “inner air” (tib. rlung) that travels through the “subtle channels” (tib. rtsa) of the body’s psycho-physical systems; and it is also the practice of releasing prayer papers into the wind, trusting their movement to disperse aspiration and dispel obstruction. This work presents a figure wearing the “chungbala chyukti” attire of the Rang (or Byasi Sauka) Tibetan community living three valleys stretching between India’s Puithoragarh district and Nepal’s Sudurpashchim province. The Northern end of the three valleys lies at the center of the Kalapani territorial dispute and has been an unsolved consequence of the 1816 Treaty of Sugauli, which attempted to divide the land by locating the “true” source of the Kali River, resulting in Rang community divided under two administrations. I do not claim to represent them; rather, their circumstances open up a broader question: when powers assign bodies to cartographic positions, what forms of movement and meaning remain impossible to contain?